Breathing training for dysfunctional breathing in asthma: taking a multidimensional approach - Rosalba Courtney (ERJ Open Research, 2017)
Various breathing training programmes may be helpful for adults with asthma. The main therapeutic aim for many of these programmes is the correction of dysfunctional breathing. Dysfunctional breathing can be viewed practically as a multidimensional entity with the three key dimensions being biochemical, biomechanical and psychophysiological. The objectives of this review are to explore how each of these dimensions might impact on asthma sufferers, to review how various breathing therapy protocols target these dimensions and to determine if there is evidence suggesting how breathing therapy protocols might be optimised. Databases and reference lists of articles were searched for peer-reviewed English language studies that discussed asthma or dysfunctional breathing and various breathing therapies. Biochemical, biomechanical and psychophysiological aspects of dysfunctional breathing can all potentially impact on asthma symptoms and breathing control. There is significant variation in breathing training protocols and the extent to which they evaluate and improve function in these three dimensions. The various dimensions of dysfunctional breathing may be of greater or lesser importance in different cases and the effectiveness of breathing training protocols is likely to be improved when all three dimensions are considered. Outcomes for breathing training for dysfunctional breathing in asthma may be most successful when the three key dimensions of dysfunctional breathing are evaluated at the start of treatment and monitored during treatment. This allows breathing training protocols to be adjusted as appropriate to ensure that treatment is sufficiently comprehensive and intensive to produce measurable improvements where necessary.